098 Developing new therapeutic strategies for inclusion body myositis. Issue 3 (9th February 2012) - Miller, A; Ahmed, M; Hanna, M G; Greensmith, L
Abstract : Sporadic Inclusion Body Myositis (IBM) remains without proven treatment, reflecting a previous lack of preclinical disease models on which to evaluate potential therapies. We developed a panel of pathological outcome measures, using primary satellite cell cultures, that reflects the multifaceted pathogenesis of IBM. This allowed initial assessment of Heat Shock Response manipulation as a new therapeutic strategy for IBM. Over-expression of β-Amyloid Precursor Protein or exposure to inflammatory mediators IL1β, TNFα and IFNγ reproduced salient features of the cellular environment found in IBM. Myotubes demonstrated ubiquitinated intracellular inclusions, increased expression of MHC Class I, mitochondrial dysfunction and cytoplasmic translocation of TDP-43. ER stress and activation of the NFκB cascade, proposed to be central pathogenic mechanisms in IBM, were also observed. We developed quantifiable measures of these changes, allowing the impact of drugs to be tested. The effects of heat shock response augmentation using Arimoclomol, a co-inducer of the transcription factor HSF-1 that drives expression of cytoprotective endogenous Heat Shock Proteins, were examined on this model. Arimoclomol treatment ameliorated several IBM-relevant features, represented by reduced inclusion formation, reduced ER stress, inhibition of the NFκB cascade, reduced cytoplasmic translocation of TDP-43 and improved mitochondrial function. We have advanced Arimoclomol into a Phase IIa study in IBM patients.